1993
DOI: 10.1148/radiology.188.1.8511281
|View full text |Cite
|
Sign up to set email alerts
|

Validation of tagging with MR imaging to estimate material deformation.

Abstract: Myocardial tagging with magnetic resonance imaging is useful for non-invasive estimation of in vivo heart wall deformation. To validate the method of strain estimation and quantify the error of deformation estimates, a deformable silicone gel phantom in the shape of a cylindrical anulus was built and imaged. Four observers digitized the displacement of magnetic tags in two deformation modes: axial shear, caused by a 45 degrees rotation of the inner cylinder, and azimuthal shear, caused by a 13.5-mm longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(100 citation statements)
references
References 17 publications
1
99
0
Order By: Relevance
“…In previous work, Moore et al (26) studied the precision of strains computed by tracking the intersection of radial tags with myocardial contours, and Young et al (27) studied the precision of two-dimensional strains computed using finite element analysis in a deforming phantom. Although both of these studies quantified strain estimate precision, they did not quantify the spatial resolution of the estimates or study the variation in spatial resolution as a function of tag separation and the number of tag plane angles.…”
Section: • Discussionmentioning
confidence: 99%
“…In previous work, Moore et al (26) studied the precision of strains computed by tracking the intersection of radial tags with myocardial contours, and Young et al (27) studied the precision of two-dimensional strains computed using finite element analysis in a deforming phantom. Although both of these studies quantified strain estimate precision, they did not quantify the spatial resolution of the estimates or study the variation in spatial resolution as a function of tag separation and the number of tag plane angles.…”
Section: • Discussionmentioning
confidence: 99%
“…The regional deformations of the myocardium were then characterized by using homogeneous finite strain analysis on the deforming triangles 6,17,18,24 -27 with the strain software module of VIDA. 21 This methodology has been validated in a phantom 14 and used in vivo by Young et al 27 These studies demonstrated that homogeneous strain analysis produced unbiased estimates of the principal strains, principal angles, and orientations of the principal axes.…”
Section: Image and Data Analysismentioning
confidence: 99%
“…Both approaches are easily applicable on standard clinical scanners. Data acquired with tagging provide information with respect to muscle deformation (2,3,(9)(10)(11)(12)(13)(14)(15)(16). While easy to visualize and implement, tagging methods suffer from low spatial resolution.…”
mentioning
confidence: 99%